A multiple criteria decision‐making approach to the selection of concrete pumps - Ulubeyli, Serdar; Kazaz, Aynur (Journal of Civil Engineering and Management, 2009)
In this study, the ELECTRE III method, which is one of the most common techniques among multiple criteria decision‐making (MCDM) approaches, was considered in a selection problem of concrete pumps. As a methodological framework, a two‐step questionnaire survey was conducted by 70 firms that have and use concrete pumps. A solution of the problem was then found in the light of the real world data by means of ELECTRE III. The paper can be of value to researchers studying the anatomy of decision‐making in equipment selection in general and investigating selection criteria of concrete pumps in particular. It also contributes to the academic environment as an application practice of ELECTRE III to correspond with the nature of equipment selection and as an effective means for the formalization of knowledge possessed by industrial practitioners. On the practical side, ELECTRE III offers an efficient and convenient tool that forces the users into orderly and methodical thinking, and guides them in making logical and robust decisions. In addition, the example illustrated in the present study can be helpful for decision‐makers dealing with similar equipment selection issues. Santrauka Šio tyrimo ELECTRE III metodas – vienas dažniausiai taikomų metodų iš daugiatikslių sprendimo priėmimo metodų – buvo pritaikytas betono siurblių parinkimo uždaviniui spręsti. 70 įmonių buvo apklaustos dviem etapais. Tuomet buvo išspręstas realus uždavinys realiais duomenimis, taikant ELECTRE III metodą. Straipsnis gali būti naudingas tyrėjams, nagrinėjantiems įrenginių parinkimo uždavinių prigimtį ir esmę. Šis straipsnis turi akademinę ir praktinę vertę, nes išreiškia efektyvių sprendimų priėmimo proceso esmę ir pateikia tvirtą sprendimo priėmimo pagrindą. Pateiktas praktinio uždavinio sprendimas yra gera metodinė priemonė parenkant statybinius mechanizmus. First Published Online: 14 Oct 2010 Reikšminiai žodžiai: betono siurblys, statybinis įrengimas, ELECTRE III, daugiatikslis sprendimų priėmimas, parinkimas.